2017
DOI: 10.1111/bjd.15736
|View full text |Cite
|
Sign up to set email alerts
|

Familial seborrhoeic keratosis associated with multiple ‘pure reticulated acanthomas’ and infundibulocystic basal cell carcinomas

Abstract: We characterize for the first time the clinical, dermoscopic and histopathological features of multiple reticulated acanthomas without apocrine or sebaceous differentiation, for which we propose the term 'pure reticulated acanthoma', and ICBCCs associated with familial seborrhoeic keratosis. We identified FGFR3 and PTCH1 germline polymorphisms whose influence in the development of reticulated acanthomas is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, this mutation is insufficient to cause cancer. Increased FGFR3 activity promotes FOXN1‐mediated differentiation and results in a benign SK‐like phenotype in previously malignant squamous cell carcinoma (SCC) cells, which may be explained by a positive FGFR3/FOXN1 feedback loop in SK 17 . FOXN1 knockdown, on the other hand, increases oncogenic RAS and causes SCC‐like cancers 18 .…”
Section: Pathogenesismentioning
confidence: 99%
“…However, this mutation is insufficient to cause cancer. Increased FGFR3 activity promotes FOXN1‐mediated differentiation and results in a benign SK‐like phenotype in previously malignant squamous cell carcinoma (SCC) cells, which may be explained by a positive FGFR3/FOXN1 feedback loop in SK 17 . FOXN1 knockdown, on the other hand, increases oncogenic RAS and causes SCC‐like cancers 18 .…”
Section: Pathogenesismentioning
confidence: 99%
“…One study by Martinez et al looked at patients with familial seborrheic keratoses associated with multiple infundibulocystic BCCs and acanthomas and identified PTCH1 and FGFR3 germline polymorphisms suggesting a possible link in the development of these lesions. 21 Another study demonstrated an association of multiple BFH FIGURE 3. Biopsies of all of the lesions showed similar histologic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MAC is often misdiagnosed as a benign adnexal tumor (such as syringoma and trichoepithelioma, which also usually appear on the face [ 5 ]) both clinically and pathologically [ 6 , 7 ]. On the other hand, disfiguring surgical excision is used to achieve clear margins because of the deeply infiltrative growth, while infundibulocystic basal cell carcinoma, a basal cell carcinoma with histologically adnexal differentiation [ 8 ], often needs to be identified with MAC, because of its good prognosis and no need for an extended margin surgery. Both of these things lead to delayed treatment and patients suffering larger wounds.…”
Section: Introductionmentioning
confidence: 99%